MENINGKATKAN VOCABULARI SISWA DENGAN MENGGUNAKAN MEDIA FLASHCARD PADA PEMBELAJARAN BAHASA INGGRIS - Rahmayanti Rahmayanti (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The aims of this research is to describe the teaching vocabulary by using flash cards media at the five grade students of SDN Pulau Kerumputan. The research design is descriptive qualitative research. There are many instruments of the research, they are the researcher herself, hand phone, laptop, camera, syllabus, lesson plan, material, and text book. The researcher can collect the data from the observation, interview and document analysis. To analyze the data, the researcher did two steps, they are the data reduction, the data representation/display, and the drawing conclusion. The result of research is found that the students’ problem in using word flashcard media in teaching and learning process in the classroom with 30 students. there are 8 students who get score 60 or average. They still have difficulty with using word flash cards. The all students understand the meaning in the picture flashcard shown by the teacher. The teacher give students score is very good with 70 - 100 score because the students can pass the KKM (Kriteria Ketuntasan Minimal). Key words: vocabular, media flashcard, SDN Pulau Kurumputan.